(untitled) (Innovative professional education, 2023)
The article raises the issue of implementing public-private partnerships in vocational (professional and technical) education at the regional level in the municipal vector, reveals the importance of the all-Ukrainian experiment in improving the process of forming soft and hard skills among students. The experience of organizing the work of educational and practical centers using the main forms of cooperation with business partners is highlighted.